The Existence of The Sukuraga Puppet In Sukabumi - Nabila, Ashila Rahma (PT. Alahyan Publisher Sukabumi, 2023)
Sukuraga Puppet is a typical Sukabumi art that combines various aspects of art ranging from visual arts, music, puppet theater and literature. This Puppet Sukuraga does not refer to most puppet literacy like the Ramayana and Mahabarata traditions. Having a unique story, being a Sukuraga Puppet has its own cultural value, but unfortunately the existence of this Sukuraga Puppet is still not known by the residents, that's why research is to find out how many people do not know about Sukuraga Puppet and what causes it. This research is a research using quantitative research methods. The data collection process originates from a questionnaire addressed to thirty respondents.